Tracking women`s reproductive data in sport: practical limitations, perils and pitfalls - Casto, K. V. (Sports Medicine, 2022)
In 2019, the US women`s national team won gold in the FIFA Women`s World Cup. Following this conclusion, a flurry of news articles [1,2,3] revealed one of the team`s sport-science innovations that contributed to their winning performance: period tracking … "one of many strategies that we deployed that helped us win". With headlines like "USWNT [US women`s national team] used innovative period tracking to help player performance at World Cup" [1] and "How period tracking can give all female athletes an edge" [3], the message to sport-science practitioners and coaches, elite and amateur athletes alike, beckons: menstrual cycle tracking can help female athletes perform and succeed!